1996
DOI: 10.1139/x26-007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial autocorrelation of allozyme traits in a Norway spruce (Piceaabies) population

Abstract: Using isoenzymes as gene markers and spatial autocorrelation analysis as a tool to detect spatial patterns, we studied the spatial distribution of genotypes in a naturally regenerated uneven-aged Norway spruce (Piceaabies (L.) Karst.) stand on the eastern Italian Alps. In most cases we found a random distribution of genotypes in space; in the whole data set less than 11% of genotype pairs showed positive associations for the first (10 m) distance class. Extensive gene flow, due to long distance dispersal of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 0 publications
4
23
1
1
Order By: Relevance
“…In two French populations only five out of 35 and two out of 20 significant SNDs were found. Similar patterns have been found for the coniferous species Pinus contorta (Epperson & Allard, 1989), Picea mariana (Knowles, 1991), Picea abies (Leonardi et a!., 1996) and for the broadleaved species Acer saccharum (Perry & Knowles, 1991;Young & Merriam, 1994), Quercuspetraea and Q. robur (Bacilieri et al, 1994). In this study most genotypes were apparently randomly located within the population.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In two French populations only five out of 35 and two out of 20 significant SNDs were found. Similar patterns have been found for the coniferous species Pinus contorta (Epperson & Allard, 1989), Picea mariana (Knowles, 1991), Picea abies (Leonardi et a!., 1996) and for the broadleaved species Acer saccharum (Perry & Knowles, 1991;Young & Merriam, 1994), Quercuspetraea and Q. robur (Bacilieri et al, 1994). In this study most genotypes were apparently randomly located within the population.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were obtained in other forest tree species: Picea mariana (Knowles, 1991), Acer saccharum (Perry & Knowles, 1991), Quercus petraea and Q. robur (Bacilieri ci' a!., 1994). Studies with intensive sampling of relatively limited areas also revealed scarce spatial structuring in lodgepole pine (Epperson & Allard, 1989), Picea abies (Leonardi et al, 1996) and Turkey oak (Berg & Hamrick, 1995).…”
mentioning
confidence: 99%
“…Other work reported nearly random spatial structure, consistent with long-distance seed and pollen dispersal, except for a few loci that could be influenced by selection in some cases (Epperson & Allard, 1989;Knowles, 1991;Geburek & Tripp-Knowles, 1994;Leonardi et a!., 1996). Lastly, Boyle et a!.…”
Section: Introductionmentioning
confidence: 65%
“…Our results are also similar to those obtained in earlier studies on P. abies. Leonardi et al (1996) found a weak spatial structure in a naturally regenerated uneven aged alpine stand, evidence of high gene flow. Scotti et al (2008) in a mixed alpine stand found high gene flow via pollen and more spatially limited seed dispersal.…”
Section: Discussionmentioning
confidence: 93%